INTEGRATING EDTECH STARTUPS INTO HIGHER EDUCATION TO OVERCOME INSTITUTIONAL DISCONNECTS - Mirjalol Mirsobitov (Innovate Conferences, 2025)
While EdTech startups are transforming educational delivery worldwide, their integration into higher education institutions (HEIs) remains uneven, particularly in developing contexts such as Uzbekistan. This thesis investigates the disconnection between EdTech startups and HEIs, identifying structural, policy-related, and cultural barriers that hinder effective collaboration. Comparative case studies from Uzbekistan, the United States, and India reveal a wide spectrum of engagement practices. In Uzbekistan, despite growing demand for digital tools post-COVID-19, universities often lack frameworks to systematically integrate domestic EdTech solutions. Meanwhile, countries like the U.S. and India present models of university-startup collaboration that foster innovation and skill development. The study concludes by proposing actionable policy recommendations to bridge the gap and strengthen Uzbekistan’s digital education ecosystem.